2021
DOI: 10.1039/d1cc01381e
|View full text |Cite
|
Sign up to set email alerts
|

Acyl fluorides as direct precursors to fluoride ketyl radicals: reductive deuteration using SmI2 and D2O

Abstract: A highly chemoselective reductive deuteration of acyl fluorides to provide α,α-dideuterio alcohols with exquisite levels of deuterium incorporation was developped using SmI2 and D2O as deuterium source. This method introduces...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The optimization studies demonstrated that the yield of 2a was influenced by the amount of both SmI 2 and D 2 O, while excellent deuterium incorporations were uniformly obtained under all the tested conditions. In this SET reductive deuteration reaction, D 2 O was both the deuterium donor and the ligand for SmI 2 [31][32][33][34][35][36]. When 5 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization studies demonstrated that the yield of 2a was influenced by the amount of both SmI 2 and D 2 O, while excellent deuterium incorporations were uniformly obtained under all the tested conditions. In this SET reductive deuteration reaction, D 2 O was both the deuterium donor and the ligand for SmI 2 [31][32][33][34][35][36]. When 5 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…While the usage of Et 3 N as the ligand improved the reduction potential of SmI 2 , it decreased the chemoselectivity of those methods [ 25 , 26 , 27 , 28 , 29 , 30 ]. Et 3 N can only be avoided by using activated carboxylic acid derivatives, such as uncommercially available pentafluorophenyl esters and acyl fluorides [ 31 , 32 ]. In this study ( Scheme 1 C), we discovered that widely available acyl chlorides are more reactive ketyl precursors which are susceptible to SmI 2 -D 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, during the course of developing Sm/SmI 2 as a new activator of carboxylic acid derivatives, An and co-workers found that acyl fluorides were compatible with such a system (Scheme 55 ). 103 Single-electron transfer of acyl fluorides would generate ketyl radicals, which are then deuterated by D 2 O to give a wide variety of α,α-dideuterated alcohols with a broad substrate scope. In particular, this strategy was used to achieve the deuteration of a series of compounds that could potentially be used as drugs and agrochemicals, and it was found that a high incorporation of deuterium could be accomplished under various conditions.…”
Section: Miscellaneous Examplesmentioning
confidence: 99%
“…It was not until Kagan [10] introduced samarium diiodide into organic synthesis that samarium diiodide (SmI 2 ) attracted the attention of many chemists as a single electron reduction reagent [11] . In the past few decades, samarium diiodide has been reported to be able to reduce carboxylic acids and their derivatives to alcohols, [12] such as esters, [12c,d] acid fluorides [12e] and amides [12f,g] . Among them, the reduction of amides is more special.…”
Section: Introductionmentioning
confidence: 99%